Dynamic plantar pressure and ground reaction force during pregnancy: A prospective longitudinal study. Issue 1 (1st January 2019) - Hamada, Hamada Ahmed; Mosaad, Dalia; Fahim, Manal; Abd El-Samea, Gehan; Youssef, Amel; Gouda Matar, Ayman
Abstract: Purpose : The purpose of this study was to investigate the changes in dynamic plantar foot pressure distribution and vertical ground reaction force in normal pregnant women at their three different trimesters. Participants and methods : Nineteen normal primigravida pregnant women in their first trimester. Participants completed three trials across the plate walkway. Outcomes Measures : The primary outcome was the peak plantar foot pressure distribution under the big toe, first and fifth metatarsal heads, the heel while the secondary outcome was vertical ground reaction force normalized to the units of body weight. There were measured by RS Foot Scan in three different trimesters of pregnancy for both feet. Results : Repeated-measures analysis of variance showed a significant increase (P < 0.05) in the plantar foot pressures under heel, first and fifth metatarsal heads, and big toe between first and either second or third trimesters as well as between second and third trimesters of pregnancy for all areas except heel at both feet. Additionally, there was a significant increase in the first peak of vertical ground reaction force normalized to the units of body weight between first and third trimesters as well as between second and third trimesters at both feet. There was a significant increase in the second peak of vertical ground reaction force normalized to the units of body weight between first and either second or third trimesters at both feet. Conclusion : Pregnancy is accompanied by changes in both dynamic plantar pressure distribution and vertical ground reaction force normalized to the units of body weight.